The Effect of Dry Cupping Therapy on Reducing Pain in Elderly Osteoarthritis Patients in Nursing Homes - Jea Anjung Pensan Elsara; Sukardin; Ni Made Sumartyawati; Rahmani Ramli (Nurse Point: Journal of Nursing, 2025)
Background: Osteoarthritis is a prevalent condition among the elderly, leading to joint pain. Treatment options for osteoarthritis can include both pharmacological and non-pharmacological therapies. One promising non-pharmacological approach is dry cupping therapy. Purpose: This study aims to evaluate the effect of dry cupping therapy in reducing pain levels among the elderly in nursing homes. Methods: The research employed a pre-experimental design utilising a one-group pre-test and post-test approach. The sample consisted of all 26 elderly residents diagnosed with osteoarthritis at the nursing home. The intervention involved administering cupping therapy to the knee for 40 minutes. Pain levels were assessed using the Bourbanis scale before and after the intervention, and data were analysed using the Wilcoxon Signed Rank Test. Results: The findings revealed a significant reduction in pain levels following the cupping therapy, with a p-value of 0.000, below the significance threshold of 0.05. This indicates that dry cupping therapy may be an effective complementary treatment for alleviating pain in elderly individuals suffering from osteoarthritis in the nursing home. Conclusion and recommendation: This study concludes that dry cupping therapy effectively reduces pain in elderly patients with osteoarthritis. Therefore, this therapy can be considered a safe and practical non-pharmacological method for managing joint pain related to osteoarthritis.